Salmonella enterica relies on carbon metabolism to adapt to agricultural environments - Han, Min; Schierstaedt, Jasper; Duan, Yongming; Nietschke, Monika; Jechalke, Sven; Wolf, Jacqueline; Hensel, Michael; Neumann-Schaal, Meina; Schikora, Adam (Frontiers in Microbiology, 2023)
Foodborne and human pathogen Salmonella enterica is a constant threat to human health. Agricultural environments, for example soil and plants, can be ecological niches and vectors for Salmonella transmission. Salmonella persistence in such environments increases the risk for consumers. Therefore, it is worthy to investigate the mechanisms used by Salmonella to adapt to agricultural environments. We assessed the adaptation strategy of S. enterica serovar Typhimurium strain 14028s to agricultural relevant situations, by analyzing the abundance of intermediates in glycolysis and the tricarboxylic acid pathway in tested environments (diluvial sand soil suspension and leaf-based media from tomato and lettuce), as well as in bacterial cells grown in such conditions. By reanalyzing transcriptome data of Salmonella grown in those environments and using an independent RT-qPCR approach for verification, several genes were identified important for persistence in root or leaf tissues, including the pyruvate dehydrogenase subunit E1 encoding gene aceE. In vivo persistence assay in tomato leaves confirmed the crucial role of aceE. Mutant in another tomato leaf persistence related gene, aceB, encoding the malate synthase A, displayed opposite persistence features. By comparing metabolites and gene expression of the wild type strain and its aceB mutant, fumarate accumulation was discovered as a potential way to replenish the effect of aceB mutation. Our research interprets the mechanism of S. enterica adaptation to agriculture by adapting its carbon metabolism to the carbon sources available in the environment. These insights may assist in the development of strategies aiming at diminished Salmonella persistence in food production systems.